Linguistics and Literature - Possible Dialogues - Rosa, Camila de Fátima; Guerra, Maria José; Silveira, Marcelo (Revista Letras Raras, 2025)
The relationship between linguistics and literature has been the subject of debate since the emergence of Language Sciences in the 20th century, revealing similarities and tensions between discourse studies and form studies. This article proposes a critical reflection on these interrelationships, based on two distinct and complementary theoretical frameworks. On the one hand, we explore the contribution of Roman Jakobson, representative of the Prague School, who analyzes the poetic function of language from a structural-functionalist perspective. On the other hand, we examine the approach of Brazilian linguist Maria Helena de Moura Neves, who uses literary texts as a starting point to explain grammatical and pragmatic mechanisms of language in use. The research, which is bibliographic in nature, draws on the analysis of literary excerpts by authors such as Paulo Leminski, Ricardo Ramos, and Machado de Assis. The study highlights how the poetic function, in Jakobson, and the metalinguistic function, in Moura Neves, establish a two-way street between literature and linguistics, in which both areas contribute to the understanding of language phenomena.